Kajian Hukum Atas Gugatan Penetapan Pasangan Calon Oleh Komisi Pemilihan Umum Dalam Proses Pemilihan Kepala Daerah Langsung (Studi Kasus Putusan Mahkamah Agung Nomor 244 K/TUN/PILKADA/2018) - Ja’far Ja’far (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
Abstract Election of Regional Head is an embodiment of Article 1 Paragraph (2) of the Constitution. Through the elections, the people can determine who will determine their position as regional head. Therefore, in the implementation of the elections, it must be carried out directly, publicly, freely, confidentially, honestly and fairly in order to guarantee the purity of people's sovereignty. As for the problems in this paper are regional head elections in the Indonesian constitutional system, the mechanism for resolving regional head election disputes in the legislation, as well as judges' considerations in regional head election disputes in the Supreme Court ruling No. 244 K / TUN / PILKADA / 2018?This research is descriptive with a normative juridical approach.